Produtividade e qualidade da cebola sob níveis de irrigação por gotejamento e doses de potássio - Barreto, Herlon Bruno Ferreira (2015)
This study aimed to evaluate the productivity and quality of onion bulbs in function of potassium doses and drip irrigation levels. The experiment was conducted under field conditions on construction sites, in the experimental area of the Department of Engineering at the Federal University of Lavras, in Lavras, which is situated in the southern region of Minas Gerais. It was used the randomized block design in a factorial 4 x 4, resulting 16 treatments repeated three times. The treatments consisted of four irrigation levels, based on the "Class A" tank evaporation (ECA) (L1 = 30 % ECA; L2 = 65 % ECA; L3 = 100 % of ECA and L4 = 135 % of ECA), and four potassium doses, corresponding to: K1 = 0; K2 = 80; K3 = 160; K4 = 240 kg ha -1 of K 2O, provided by fertigation. The crop was harvested when more than 60 % of the plants were cracked, and is realized manually. We conducted the evaluation of the following: total productivity bulbs, commercial bulbs productivity, average mass of commercial bulbs, efficient use of water, dry matter of commercial bulbs content determination of pH, total soluble solids, total acidity, soluble solids / titratable acidity and post-harvest conservation. The irrigation levels influenced increasingly the following characteristics: total productivity bulbs, productivity of commercial bulbs and average mass of commercial bulbs, the maximum value of commercial bulbs productivity occurred with the water replacement fraction of 135 % ACE (795.6 mm), resulting in 51.2 t ha -1 . The potassium doses showed a significant response to the characteristics: dry matter content of commercial bulbs and pH. The interaction between irrigation levels and potassium doses showed significant response in relation to the characteristics: efficiency in water use, titratable acidity and total soluble solids / total acidity. Mass losses for the postharvest bulbs were influenced by the factor days after healing, increasingly. The maximum being found of 8.31 %. The hybrid Bella Vista had good postharvest conservation, being an alternative to in-kind consumption. Drip irrigation has provided more efficient absorption of potassium in the soil, explaining the applied potassium doses did not show significant results.